The HDAC Inhibitors Trichostatin A (TSA) and Suberoylanilide Hydroxamic Acid (SAHA) Exhibit Multiple Modalities of Benefit for the Vascular Pathology of Sickle Disease - Hebbel, Robert P; Vercellotti, Gregory M.; Pace, Betty; Solovey, Anna; Kollander, Rahn; Abanonu, Chine; Nguyen, Julia; Vineyard, Julie V.; Belcher, John D; Abdulla, Fuad; Osifuye, Shade; Eaton, John W.; et al. (Blood, 2009)
Abstract 2586 Poster Board II-562 The chronic, inflammatory vasculopathy of sickle cell anemia accounts for much of the non-infectious morbidity and mortality of this disease. The pathogenesis of vasculopathy involves multiple sub-biologies (sickling, hemolysis, inflammation, adhesion, coagulation, NO deficiency, stasis, and reperfusion injury). Moreover, these various sub-biologies overlap and transactivate each other. So a single modality approach would very likely fail to be effective. For this reason, effective preventative and interventional therapy for sickle vasculopathy will very likely require true multi-modality therapy, preferably with as few drugs as possible. To this end, we have evaluated the histone deacetylase (HDAC) inhibitors TSA and SAHA for beneficial vascular effects in sickle transgenic mouse models. We used the hBERK1 mouse, which displays abnormal endothelial activation even at ambient air; and we used the NY1DD mouse which only acquires significant endothelial activation upon exposure to hypoxia/reoxygenation. Both drugs significantly inhibited the abnormal endothelial expression of tissue factor, predicting beneficial effects for sickle coagulopathy. Both drugs significantly inhibited abnormal endothelial expression of VCAM1, a molecule involved in both adhesion and inflammation sub-biologies. Both drugs worked in both mouse models. For these benefits, both drugs were effective when given as preventative therapy (NY1DD model) or as longer term therapy (hBERK1 model), although previously-established endothelial activation (e.g., the hBERK1 model) required long term (3 weeks) therapy to observe the most significant benefits. TSA markedly inhibited the vascular stasis in the dorsal skinfold chamber model of hBERK1 mice that is seen after their exposure to H/R; SAHA did so in S+SAntilles mice after H/R; our previous studies have implicated VCAM1 and abnormal cell/cell interaction as the etiology of stasis in this model. Both drugs induced gamma globin and levels of HbF in K562 cells in vitro. Both drugs exhibited activity as iron chelators, as detected by absorption spectra in vitro. Since both drugs are hydroxamic acids, they may promote NO formation by the same mechanism that hydroxyurea is said to work, although we did not test this. We suggest that SAHA, which is already approved for other human clinical use, should be considered for testing in a pilot study to determine drug tolerance and in vivo efficacy in sickle subjects. No relevant conflicts of interest to declare.